CRISES AND INNOVATIVE SOLUTIONS IN MANAGEMENT PSYCHOLOGY (Ustozlar uchun, 2025)
This study explores the major psychological crises emerging in modern management and examines innovative solutions that enhance leadership effectiveness and organizational stability. The rapid development of digital technologies, shifting workplace structures, and increasing emotional pressure on employees have intensified the need for psychologically informed managerial approaches. Key challenges such as resistance to change, communication barriers, burnout, and reduced motivation are analyzed to highlight their impact on organizational performance. The paper emphasizes the role of emotional intelligence, adaptive leadership, coaching, and data-driven strategies as effective tools for addressing these issues. The findings suggest that integrating innovative psychological methods into management practices can significantly improve decision-making, strengthen team collaboration, and increase overall productivity.